Empowering Mathematics Teachers In Evaluating Textbooks: A Praxeological Approach To Enhancing Constructive Skepticism - Agus Hendriyanto; Ayi Abdurahman; Wiwin Winarni; Utomo Utomo; Sajidin Sajidin; Deasy Fatmasari; Elsya Syaifana; Lukman Hakim Muhaimin (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to empower mathematics teachers in evaluating textbooks through the praxeological approach and the development of a constructive skepticism attitude. Textbooks are often used without critical evaluation, which can hinder the development of students' critical thinking skills. The praxeological approach provides a framework based on practical experience, while constructive skepticism encourages in-depth analysis of textbook content. The study employed a qualitative method with a hermeneutic phenomenological approach, involving 20 mathematics teachers in Sukabumi. Data were collected using semi-structured interviews and questionnaires, which explored teachers' criteria for textbook evaluation, challenges in using textbooks, and their attitudes toward textbook content. Thematic analysis was used to analyze the data, allowing the identification of patterns and themes related to teachers' evaluation practices. The results showed that training based on praxeology and constructive skepticism improved teachers' ability to evaluate textbooks, identify weaknesses, and select more relevant materials. This study recommends collaborative training programs to support more critical textbook evaluations, with the goal of enhancing the quality of mathematics education in Indonesia.